Sensorless motor control in application of electric vehicles - Teng, Pang Sheng (Nanyang Technological University, 2023)
Due to the advantages for the environment, the use of electric vehicles has been receiving more attention in the recent years. The motor control system is a crucial component of electric vehicle technology. Sensors have been utilized by motor control systems in the past to offer feedback on the position and speed of the motor. However, sensor-based control systems can be pricey, heavy, and prone to malfunction, particularly under harsh environmental conditions. As a result, sensorless motor control solutions for electric vehicles are gaining popularity. Without the use of physical sensors, sensorless motor control uses software and algorithms to determine the position and speed of the motor. This strategy can lower costs and complexity while enhancing reliability. The use of sensorless motor control in electric cars is the main topic of this report. The implementation of field-oriented control (FOC) approaches for sensorless motor control is specifically explored. With the use of a well tuned FOC, three type of observers will be designed to compare the esimated speed and position values observed, against the reference values. The three type of observers are namely the Extended State Observe (ESO), Disturbance Observer (DO), and Sliding Mode Observer (SMO). The performances of the three observer will be compared with the use of MATLAB Simulink, where speed and position graphs will be compared to judge the performance of the three observers. The best performing observer will be chosen for the replacement of the encoder in the sensorless control. The implementation of the replacement of encoder with the 3rd order ESO observer was deemed successful since the dynamics of the system did not differ much from the observed speed by the encoders.